Serial lipase for pancreatitis: not enough evidence. Issue 6 (28th November 2017) - Pathmarajah, Tishanthan; Idrees, Marwan; Nasim, Sana; Weber, Dieter G.
Abstract : Background: Lipase is both a sensitive and specific marker for diagnosing pancreatitis. However, the benefit of serial lipase in both monitoring and defining prognosis remains undetermined. This systematic review was conducted to further evaluate this potential application. In addition, this review also looked into the benefits of serial lipase in the subgroup of traumatic pancreatitis. Methods: PubMed, Cochrane Library and Google Scholar were systematically searched for related articles, between January 1995 and December 2015, according to Preferred Reporting Items for Systematic Reviews and Meta‐analyses standards. Data was extracted and analysed by two authors. Results: Seven studies were included in the final analysis: six retrospective and one prospective studies were identified. Five studies (all retrospective) concluded no benefits in serial lipase for prognostication, while two studies identified serial lipase as a beneficial prognostic factor for acute pancreatitis. Of the included studies, only two involved traumatic pancreatitis (both dedicated to the paediatric population). Conclusion: The evidence supporting or opposing serial lipase as a prognostic factor for pancreatitis is weak and consists mainly of retrospective analyses. The only prospective data identified suggested benefits to serial lipase in prognosis. Further prospective studies evaluating the prognostic value of serial lipase in the adult population with both traumatic and non‐traumatic pancreatitis are required given the paucity of available evidence.